2005
DOI: 10.1016/j.jmb.2005.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Receipt of the C-terminal Tail from a Neighboring λ Int Protomer Allosterically Stimulates Holliday Junction Resolution

Abstract: Bacteriophage λ integrase (Int) catalyzes the integration and excision of the phage λ chromosome into and out of the Esherichia coli host chromosome. The seven carboxy-terminal residues (Cterminal tail) of Int comprise a context-sensitive regulatory element that links catalytic function with protein multimerization and also coordinates Int functions within the multimeric recombinogenic complex. The experiments reported here show that the β5-strand of Int is not simply a placeholder for the C-terminal tail but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The Flp‐related tyrosine recombinases Cre, lambda Int and XerC/XerD resemble vaccinia topoisomerases in that each houses its active site within a protein monomer. Nevertheless, the full chemical competence and functional regulation of the cis active site may require trans allosteric activation by a neighbouring monomer (Guo et al , 1997; Hallet et al , 1999; Biswas et al , 2005; Hazelbaker et al , 2005). It would be interesting to test whether Cre, Int and XerC/XerD are more Flp‐like or topoisomerase‐like in regards to the reaction steps that are prone to hydrolysis and whether they use phosphate electrostatics or active site electrostatics to deal with this encumbrance.…”
Section: Discussionmentioning
confidence: 99%
“…The Flp‐related tyrosine recombinases Cre, lambda Int and XerC/XerD resemble vaccinia topoisomerases in that each houses its active site within a protein monomer. Nevertheless, the full chemical competence and functional regulation of the cis active site may require trans allosteric activation by a neighbouring monomer (Guo et al , 1997; Hallet et al , 1999; Biswas et al , 2005; Hazelbaker et al , 2005). It would be interesting to test whether Cre, Int and XerC/XerD are more Flp‐like or topoisomerase‐like in regards to the reaction steps that are prone to hydrolysis and whether they use phosphate electrostatics or active site electrostatics to deal with this encumbrance.…”
Section: Discussionmentioning
confidence: 99%
“…NMR data found that the tail is flexible and is not altered by the addition of a single Int monomer-binding site (65). However, activity of the wild-type monomer can be restored by adding an excess of a peptide that mimics the C-terminal tail (66). Such negative regulation may be particularly important for Int, which binds crossover site DNA with relatively weak sequence specificity.…”
Section: Controlling Catalytic Activity: Half-of-the-sites Reactivitymentioning
confidence: 99%
“…27 We expressed and purified four different protein constructs comprising fragments of the enzyme involved in core site binding and cleavage: (1) Int CB , a protein construct containing the core-binding domain of λ-Int, (2) Int CB+Cat , containing both the central and catalytic domains, (3) Int Cat , the isolated catalytic domain, and (4) Int CatΔ349C197S , a fragment of the catalytic domain bearing a Cys-Ser substitution at position 197 to improve sample behavior and lacking the last seven residues from the C terminus; these residues have been implicated in mediating inter-protomer interactions important for coordinated cleavage. 23,24,28,29 All constructs containing the catalytic domain, (i.e. Int CB+Cat , Int Cat and Int CatΔ349C197S ) were competent for site-specific cleavage of DNA half-site substrates, 6,26 with the Int CatΔ349C197S construct exhibiting slightly increased activity 24 and improved stability compared to Int Cat .…”
Section: Resultsmentioning
confidence: 99%